ANALYSIS OF BRAND IMAGE ON CONSUMER DECISIONS TO BUY FASHION PRODUCT ONLINE IN E-COMMERCE OF GENERATION Z AT BANDAR LAMPUNG CITY - Aprilia Tri Asifa; Hendri Rudiawan; Jhon Nasyaroeka (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine whether there is an influence between product image, user image, brand ambassador, promotion, price and product quality on consumer decisions to buy fashion product online in e-commerce of generation z at Bandar Lampung city. This study uses quantitative methods with multiple linear regression analysis. The number of samples in this study was 500. The method of collecting data is by distributing questionnaires using google forms as a medium. The results of the t test show that the product image variable has significant effect on purchasing decisions for buy fashion product with a tcount value greater than ttable (4,163 > 1,965), the user image variable has significant negative effect on purchasing decisions for buy fashion product with a tcount value greater than ttable (4,356 > 1,965), the brand ambassador variable has significant negative effect on purchasing decisions for buy fashion product with a tcount value greater than ttable (3,664 > 1,965), the promotion variable has significant effect on purchasing decisions for buy fashion product with a tcount value greater than ttable (5,255 > 1,965), the price variable has significant effect on purchasing decisions for buy fashion product with a tcount value greater than ttable (8,966 > 1,965), and product quality variables have a significant effect on purchasing decisions for buy fashion product products with a tcount value greater than ttable (11,077 > 1,965). Product image, user image, brand ambassador, promotion, price and product quality variables simultaneously affect the purchasing decisions for buy fashion product online in e-commerce of generation z at Bandar Lampung city.